2008
DOI: 10.1111/j.1365-246x.2008.03873.x
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical investigation and dynamic modelling of unstable slopes: case-study of Kainama (Kyrgyzstan)

Abstract: S U M M A R YThe presence of massive Quaternary loess units at the eastern border of the Fergana Basin (Kyrgyzstan, Central Asia) makes this area particularly prone to the development of catastrophic loess earthflows, causing damages and injuries almost every year. Efficient disaster management requires a good understanding of the main causes of these mass movements, that is, increased groundwater pressure and seismic shaking. This paper focuses on the Kainama earthflow, mainly composed of loess, which occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 23 publications
0
51
1
3
Order By: Relevance
“…Notably, in the central Tien Shan, field surveys are carried out by students in the frame of a field school organised by Strom and Abdrakhmatov (2009). Geophysical field surveys have been completed on/near a dozen of mainly earthquake-triggered mass movements; related results were presented in Master's Theses (de Marneffe, 2010;Dupont, 2011;Deprez, 2012); earlier surveys are summarized by Havenith et al (2003Havenith et al ( , 2006a, Danneels et al (2008). For sub-regions, such as the Maily-Say Valley (part of Z4 in Fig.…”
Section: Data and Methods Used For Landslide Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, in the central Tien Shan, field surveys are carried out by students in the frame of a field school organised by Strom and Abdrakhmatov (2009). Geophysical field surveys have been completed on/near a dozen of mainly earthquake-triggered mass movements; related results were presented in Master's Theses (de Marneffe, 2010;Dupont, 2011;Deprez, 2012); earlier surveys are summarized by Havenith et al (2003Havenith et al ( , 2006a, Danneels et al (2008). For sub-regions, such as the Maily-Say Valley (part of Z4 in Fig.…”
Section: Data and Methods Used For Landslide Mappingmentioning
confidence: 99%
“…On the basis of these investigations and modelling of possible trigger factors, Danneels et al (2008) concluded that this loess flow was most likely due to a combination of long-term slope destabilisation and short-term triggers. The latter include intensified water infiltration in ground fractures that may have appeared after two Ms = 4.4 and Ms = 4.5 events that occurred 2 weeks before the landslide (on April 8 and 9, 2004, at an epicentral distance of 43 and 45 km, respectively).…”
Section: Landslide Types: Loess Landslidesmentioning
confidence: 99%
“…These observations highlight the particular susceptibility of loess areas to seismic ground failure, such as it was clearly shown by Derbyshire et al (2000) analysing geological hazards affecting the loess plateau of China. In addition to those notes directly concerning the 1920 Haiyuan-Gansu earthquake, we also refer to the observations by Danneels et al (2008) who proved that a thick cover of loess (especially if present on the top of slopes) can induce strong amplification of the seismic motion. Thus, the maximum value of 4 was attributed to the 'Lithological factor' of the Haiyuan-Gansu event due to both the weak stability of loess-covered slopes and to site amplification.…”
Section: Classification Of Seismically Induced Landslidesmentioning
confidence: 99%
“…These variations have been linked to snow accumulation in the winter months, intensity of snow melting and additional precipitation during the snow melt [18,19]. Earthquakes contribute to the destabilization and can act together with the hydrometeorological factor [20].…”
Section: Study Areamentioning
confidence: 99%